Peran Pendidikan Pancasila dalam Membentuk Generasi Muda yang Berkarakter dan Berwawasan Kebangsaan - Ruwaidah, Ai Ira Siti; Salsabil, Alfi Mardiyyah; Safitri, Awalia; Hanapiah, Frisian Nur; Khotimah, Humairo Husnul; Aulia, Naifa Fae; Noviyanti, Netha Salwa; Azzahra, Siti Fatimah; Furnamasari, Yayang Furi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article discusses the importance of Pancasila education to shape the Indonesian nation and the broad-minded young generation. The research method used is a literature review. This research data is that various literature will be used, including articles, research reports, journals, books and various other appropriate sources. Data is obtained through literature search in electronic databases related to the topic and published through Google Scholar. Analysis and evaluation are carried out through qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The findings of this study are that Pancasila education is considered as a view of national life and justice that enlivens daily life and becomes the basis for the formation of the character of the younger generation. The ideal young generation is a young generation who has noble character, noble character, integrity, nationalism, and broad national insight. In this context, Pancasila education contributes to the internalization of moral and ethical principles, the formation of national and state consciousness, and the preservation of national identity and values during globalization. The results of literature analysis show that Pancasila education plays an important role in shaping the morals, integrity, and national consciousness of Indonesia's young generation